Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Numbered Heads Together terhadap Pemahaman Konsep Matematis Peserta didik Kelas VII SMPN 2 Payakumbuh - RIVELA APRIOLA (Departemen Matematika, 2019)
Mathematics concepts understanding is very fundamental which should be owned by the students. However, in reality mathematics concepts understanding the student of SMPN 2 Payakumbuh first year still low and learning process had done yet. The solution applied was coperative leaning model NHT type. The purpouse of this researrch was to describe thee comparison off students’ mathematics concept understanding who studied with cooperative learning model NHT type to the students who studied with directly learning and to describe the progressing of students’ mathematics concepts understanding to the students who studied with cooperative learning model NHT type in grade VII SMPN 2 Payakumbuh. The type of this research is quasy experiment and descriptive which is using static group design research planning and t-test hypothesis evidence. It can be concluded that from the data analysis, for the level of , mathematics concepts understanding of students who studied with cooperative learning model NHT type were better than who studied with directly learning and students’ mathematics concepts understanding fluctuated in every meeting. Keywords – NHT (Numbered Heads Together), mathematics concepts understanding